2021
DOI: 10.3390/s21020446
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Attack Classification Using Machine Learning in IoT Networks

Abstract: In recent years, there has been a massive increase in the amount of Internet of Things (IoT) devices as well as the data generated by such devices. The participating devices in IoT networks can be problematic due to their resource-constrained nature, and integrating security on these devices is often overlooked. This has resulted in attackers having an increased incentive to target IoT devices. As the number of attacks possible on a network increases, it becomes more difficult for traditional intrusion detecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 41 publications
1
87
0
2
Order By: Relevance
“…Authors in [8] reported the advancements of remote sensor organization (WSN), correspondence innovation, and IoT innovation. Authors in [9] used ML techniques such as KNN, SVM, DT, Naïve Bayes, neural networks, and RF which can be applied in IDS. The authors compared ML models for multi and binary class combinations on the data set of Bot-IoT.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in [8] reported the advancements of remote sensor organization (WSN), correspondence innovation, and IoT innovation. Authors in [9] used ML techniques such as KNN, SVM, DT, Naïve Bayes, neural networks, and RF which can be applied in IDS. The authors compared ML models for multi and binary class combinations on the data set of Bot-IoT.…”
Section: Related Workmentioning
confidence: 99%
“…Besides, users ca be notified about malicious activities. There is a challenge associated with traffic classif cation in the IoT domain because there are very few platforms that analyzes this issue [16 A limited research is done on IDS using ML deployed on IoT networks [17,18]. The pr mary reasons are the lack of datasets and also real hardware deployed for all dataset consisting of simulated IoT devices [19].…”
Section: Intrusion Detection Systems (Ids)mentioning
confidence: 99%
“…Recently, deep-machine-learning-based automated feature engineering and classification has been shown to outperform state-of-the-art, manual-feature-engineering-based shallow classification. However, both deep and shallow machine learning algorithms have widely been applied to English Corpora, with little work being carried out to develop deep learning models for Persian sentiment analysis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%